PERAN KOMUNIKASI ANTARPRIBADI DALAM KELUARGA UNTUK MENUMBUHKAN KARAKTER ANAK USIA DINI - Meni Handayani (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2016)
The involvement of family in developing academic competence and social behavior is badly needed. The role of parents particularly mother on the child of under 5 years old is very influential. The parents should keep parenting and educating their child to enable him/her socialize and communicate well. Interpersonal communication between the parents and the child is important to build the child’s character suitable to the parents’ style. The child’s character is established from the family, particularly how the parents transfer moral value, honesty, and religion to the child through good communication. The parents do not do it just by words but by behavioral modelling. The strategy of seeking information from the parents is achieved by observation and expression of the child. It is important to listen to the child’s expression. Inner character resulted from the child’s cultural background is developed from the family and community. Thus, the child can develop based on the character of his/her cultural roots. Universal education can be conducted in uniform but the culture based on local wisdom should be maintained, such as togetherness in the family, being ashamed of breaking the existing values, and being afraid of doing the wrong things.